Multi-actor regional governance: regions as new players for innovation in Europe - Knut Koschatzky; Vivien Lo (European Regional Science Association (ERSA), 2004)
In recent years, new regionally based strategy building processes emerged at the interface between public policy and the social coordination of collective action. Foresight as a governance process for stimulating regional innovation and for strengthening the regional economic system against global competition became a popular concept. Based on the experiences of a strategy building process in the Italian autonomous province of Trento, it is the objective of the paper to sketch recent theoretical and political developments regarding multi-actor and multi-level governance and policy concepts at the regional level.
Keywords: 330